The Effect of Seaweed Extract Biostimulant on Growth and Yield of Eggplant (Solanum melongena L.) - Athillah Ramadhani; Ad’Diva Ahmad Fadhil Aryodya; Putri Nabila Maharani; Dukat (Agricultural Science, 2026)
Eggplant possesses high economic value with various nutritional contents such as minerals and vitamins that are benefical for human health. However, productivity decline due to environmental stress poses a challenge in global market demand fulfillment. The application of biostimulants represents one solution to enhance the growth and yield of eggplant (Solanum melongena L.). This research aimed to examine the effect and optimal concentration of biostimulant application on eggplant plants. The study was conducted in cultivation fields located in Nanggela Village, Kuningan Regency, West Java, from July to October 2025. This experiment used Randomized Block Design (RBD) with nine biostimulant concentration treatments and three replications, resulting in 27 experimental plots, each measuring 3,5 x 1,5 meters, consisting 14 plants and a 50 cm spacing between plots, 50 cm spacing between plants, and 60 cm spacing between rows. The vegetative phase observation parameters included root length, root volume, plant height, stem diameter, number of leaves, leaf area, leaf area index, plant dry weight, and relative growth rate, while the generative phase parameters included number of fruits, fruit diameter, fruit length, fruit weight, and yield weight per plant. The data obtained were analyzed using one-way analysis of variance (ANOVA), followed by the Scott-Knott cluster analyses to determind significant differences among treatments. The results showed that biostimulants had a significant effect on growth and development aspects. Specifically, biostimulant application significantly affected both vegetative and generative parameters. The best vegetative characteristics were obtained in K1 (1,0 ml/l), K2 (1,5 ml/l), and K3 (2,0 ml/l) treatments, while the optimal generative characteristics were produced in K1 (1,0 ml/l), K2 (1,5 ml/l), K4 (2,5 ml/l), and K7 (4,0 ml/l) treatments.